2020
DOI: 10.17582/journal.pjz/20181219121245
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal Dose Reponses of Native Polyhydroviruses and Spinosad for Economical and Sustainable Management of Spodoptera litura in Pakistan

Abstract: Authors' Contribution JNA, RM and SJNA designed and conducted the experiment. RM, MAM, SJNA and JNA wrote the manuscript. JNA, MAM, IA and AMB analyzed the results. SJNA, AMB, MM, MT, ZA SM critically reviewed the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Another study tested three doses of Spinosad against 3rd and 4 th instar of S. litura to check mortality, adult emergence, and pupation. It was observed that Spinosad has a synergist effect result in high mortality and low adult emergence (Ahmad et al, 2020). The resistance step to pesticides negatively impacts the level of development on reproductive potential as minimum improvement was observed in our study for strains with a maximum resistance period.…”
Section: Discussionmentioning
confidence: 44%
“…Another study tested three doses of Spinosad against 3rd and 4 th instar of S. litura to check mortality, adult emergence, and pupation. It was observed that Spinosad has a synergist effect result in high mortality and low adult emergence (Ahmad et al, 2020). The resistance step to pesticides negatively impacts the level of development on reproductive potential as minimum improvement was observed in our study for strains with a maximum resistance period.…”
Section: Discussionmentioning
confidence: 44%